2021
DOI: 10.1093/police/paab058
|View full text |Cite
|
Sign up to set email alerts
|

Responding to the Public during a Pandemic: Perceptions of ‘Satisfactory’ and ‘Unsatisfactory’ Policing

Abstract: As part of a substantial research project on policing the Covid-19 pandemic, a public survey was conducted in Hampshire and the Isle of Wight in England. Four open-ended questions provided participants with the opportunity to produce unlimited free-text responses regarding their perception of policing during the pandemic. Responses were coded and thematically analysed to identify themes concerning public compliance and policing during the lockdown. Subthemes surrounding communication, efficiency, and equity em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
2
8
0
Order By: Relevance
“…Another key informant mentioned "I am happy with police presence in public places […] especially when police are putting themselves at risk to enforce COVID-19 rules (Interview with Key Informant 5, February 2022). This finding is similar to those found in some of the literature (e.g., Perry & Jonathan-Zamir, 2020;Boon-Kuo et al, 2021;Ghaemmaghami et al, 2021;Heidinger & Cotter, 2020;Nouri & Kochel, 2021;Sargeant et al, 2021;Sibley et al, 2020;Yang et al, 2021). When the public is faced with an emergency or threat, they respond with a general sense of cohesion and positivity (Chand et al, 2022a;Clements, 2020).…”
Section: Overall Public Satisfaction With Police Performancesupporting
confidence: 88%
“…Another key informant mentioned "I am happy with police presence in public places […] especially when police are putting themselves at risk to enforce COVID-19 rules (Interview with Key Informant 5, February 2022). This finding is similar to those found in some of the literature (e.g., Perry & Jonathan-Zamir, 2020;Boon-Kuo et al, 2021;Ghaemmaghami et al, 2021;Heidinger & Cotter, 2020;Nouri & Kochel, 2021;Sargeant et al, 2021;Sibley et al, 2020;Yang et al, 2021). When the public is faced with an emergency or threat, they respond with a general sense of cohesion and positivity (Chand et al, 2022a;Clements, 2020).…”
Section: Overall Public Satisfaction With Police Performancesupporting
confidence: 88%
“…Considerable empirical evidence has suggested that the key factor that shapes public behaviour is the fairness of the processes used by legal authorities when dealing with members of the public ( Bolger & Walters, 2019 ; Radburn & Stott, 2019 ; Tankebe, 2013 ; Terrill et al, 2016 ). In respect of policing the pandemic, studies have equally found that deploying procedurally just approaches have helped in effectively supervising COVID-19 rules ( Aborisade & Ariyo, 2022 ; Farrow, 2020 ; Ghaemmaghami, et al, 2021 ). Meanwhile, in deploying procedurally just approaches for policing the pandemic, the wider context of police-public engagement has been explored ( Ghaemmaghami, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In respect of policing the pandemic, studies have equally found that deploying procedurally just approaches have helped in effectively supervising COVID-19 rules ( Aborisade & Ariyo, 2022 ; Farrow, 2020 ; Ghaemmaghami, et al, 2021 ). Meanwhile, in deploying procedurally just approaches for policing the pandemic, the wider context of police-public engagement has been explored ( Ghaemmaghami, et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… Ghaemmaghami et al (2021, p. 2325) , argued that, moving forward, the police will have to strengthen their legitimacy again in the post-pandemic world, and while their study's respondents sympathised that the police were ‘doing their best’, the consequences of discretionary decisions are yet to be seen. HMICFRS commissioned a YouGov poll to gauge public perceptions of the police during the first nine months of the pandemic, and despite negative press, the survey found that 33% of the British public believed the police did the right amount of enforcement (or should have done more – 38%), and 33% also believed the police were effective at providing pandemic-related guidance (although 35% believed they were not effective) ( YouGov ,2020a ).…”
Section: Discussionmentioning
confidence: 99%